Adopting e-government in the promotion of good democratic values and citizens’ rights in Nigeria (2016)
Information and Communication Technologies (ICTs) have greatly impacted the world by promoting efficiency, effectiveness in communications and quick delivery of services. Almost all sectors of the society are adopting ICTs in their operations. On the political plane, the concept of e-government has been developed for effective delivery of government services to the citizenry, promoting transparency in government, and participation in policy decisions, among other things. Adoption of e-government strategies have been viewed as a key factor in the achievement of sustainable development goals. Some countries have, over time, made gradual progress in applying ICTs in their governance. This research is aimed at reviewing the scope of adoption of e-government in Nigeria vis-a-vis the standard required and in comparison with some countries that have made tremendous progress in applying e-government strategies to governance. It was realised that Nigeria still has much to do to level up with others, mostly developed countries. In view of this, implementation of right to information and other ancillary rights are not adequately promoted.